Pourquoi revient-on à ses moutons ? Un regard croisé sur la valeur sémantique du retour en français et en polonais - Sikora-Pouivet, Dorota (Studia Romanica Posnaniensia, 2006)
French verbs revenir, rentrer, retourner refer to the same kind of location situations as their Polish « doubles » wrócic/wracac. This paper analyzes their meanings through examples presented with their contextual data. Revenir and rentrer are morphologically analysable as complex lexemes derived from the corresponding venir and entrer by adding the prefix RE-. REderivation provides a semantic feature of iterativeness to these complex items. From a synchronic point of view, retourner, in the sense investigated in this article, cannot be considered anymore as RE- derived, but it lexicalizes similar values. Wracac/wrócic share some of them. Some differences in the lexical meaning of all these verbs are explained, especially by showing how they are used as pragmatic indexes inside the relation between the speaker and a reference to a location.